EXPERIENCE REPORTE: THEORETICAL AND PRATICAL KNOWLEDGE OF MECHANICAL VENTILATION IN OBESE PATIENTS DURING INTER-HOSPITAL TRANSFER - de Freitas Ferreira, Fernanda; Campos Gontijo, Laís; Leão Calumby, Laís; Almeida Honorato, Letícia (Health and Society, 2023)
This article aims to report the personal experience of the crew of the Mobile Intensive Care Unit – ICU, of a private company, in the center-west region of the state of Minas Gerais. The method used is the report of experiences lived in the last 15 months. It was noticed that the body mass index - BMI, was often not prioritized during removal requests in patients using an orotracheal tube in obese patients, as the majority of ventilators available on the market do not ventilate morbidly obese patients, generating a risk of barotrauma in bag-mask-valve ventilation. This generated in the institution a new protocol for assistance and reception by the attendant when it comes to intubated patients. As it is an Intensive Care Unit (mobile ICU) environment, it requires numerous prevention, stabilization and health promotion actions for the individual to be transported. This is a highly vulnerable vehicle for patients in transit and for the car’s crew. The article leads to reflection on the topic, providing the opportunity to have a broader view when it comes to transporting an obese patient. Despite being very specific and qualified assistance, the importance of disseminating information could awaken the community in general, as any human being could one day need this care and this type of transport. Among the ways to prevent transport complications, the measures taken include improving communication from the team leaving the support base until receiving the patient in the specialized bed with the best support.